The emerging roles of B cells as partners and targets in periodontitis - Zouali, Moncef (Autoimmunity (Chur, Switzerland), 2017)
Initial studies of periodontal disease suggested that T cell-mediated immunity against oral Gram-negative microorganisms is a key player in the pathogenesis of this inflammatory disease. Recent investigations, however, revealed that B cells are also engaged. Given their chief role in innate-like and adaptive immune responses, B cells could exert protective functions in periodontitis. However, the periodontal bacteria-specific antibody response is generally unable to halt disease progression in affected subjects, suggesting that the antibodies produced could exhibit low anti-bacterial blocking functions or opsonophagocytic potential, and/or unfavorable effects. Moreover, although microbial antigens are involved in the induction of the inflammatory responses in human adult periodontitis, endogenous antigens also may contribute to the chronicity of this common disease. Not only antibodies to self-antigens, such as collagen, are locally produced, but the autoreactivities observed in aggressive periodontitis are more severe and diverse than those observed in chronic periodontitis, suggesting that autoimmune reactivity could play a role in the tissue destruction of periodontal disease. Further support for a pathological role of B cells in periodontitis comes from the finding that B cell-deficient mice are protected from bacterial infection-induced alveolar bone loss. Studies in patients indicate that B cells and plasma cells, together with osteoclastogenic factors (RANKL and osteoprotegerin) and specific cytokines involved in their growth and differentiation (BAFF and APRIL) participate in the induction of the pathological bone loss in periodontitis. This novel insight suggests that selective targeting of B cells could represent a future therapeutic avenue for severe periodontal disease.